Results of Ten-Year Follow-Up of Alcohol Septal Ablation in Patients with Obstructive Hypertrophic Cardiomyopathy - Kashtanov, Maksim; Rzhannikova, Anastasiya; Chernyshev, Sergey; Kardapoltsev, Lev; Idov, Eduard; Berdnikov, Sergey (International Journal of Angiology, 2018)
This study looks at 10-year follow-up outcomes of alcohol septal ablation in patients with obstructive hypertrophic cardiomyopathy.Between 2000 and 2008, 40 patients with obstructive hypertrophic cardiomyopathy (27 males, 13 females) underwent alcohol septal ablation. The median follow-up period was 123 (2–179) months. The mean age ran to 43.8 + 13.9 years. The initial dose of ethanol (3 mL) was chosen for ablation in all cases.The hospital mortality was 0%. Permanent pacemakers were implanted in 3 of 40 (7.5%) cases in the hospital period. The median clinical follow-up was 123 (2–179) months. Survival rates at 1, 5, 10, and 15 years after the procedure were as follows: 97.5% (95% confidence interval [CI], 95.1–99.9%), 92.5% (95% CI, 94.8–90.2%), 85.0% (95% CI, 82.9–87.1%), and 81.3% (95% CI, 79.3–83.3%), respectively. Seven patients died during follow-up. Sudden death was observed in two cases. Permanent pacemakers were implanted in 2 of 40 (5%) cases in the follow-up. The log-rank test revealed no statistically significant difference between the 15-year survival rate in our cohort and age- and sex-matched general Russian population (p = 0.11113).Alcohol septal ablation provides long-term survival rates that look comparable with age- and sex-matched general population in the 15-year follow-up period.
Keywords: coronary intervention; cardiovascular disease; endovascular procedure; percutaneous; intramyocardial; infarction; hemodynamics